Demography of the Pacific walrus ( Odobenus rosmarus divergens ) in a changing Arctic - Rebecca L. Taylor; Mark S. Udevitz; Chadwick V. Jay; John J. Citta; Lori T. Quakenbush; Patrick R. Lemons; Jonathan A. Snyder (Marine Mammal Science, 2018)
The Pacific walrus ( Odobenus rosmarus divergens ) is a candidate to be listed as an endangered species under United States law, in part, because of climate change‐related concerns. While the population was known to be declining in the 1980s and 1990s, its recent status has not been determined. We developed Bayesian models of walrus population dynamics to assess the population by synthesizing information on population sizes, age structures, reproductive rates, and harvests for 1974–2015. Candidate models allowed for temporal variation in some or all vital rates, as well as density dependence or density independence in reproduction and calf survival. All selected models indicated that the population underwent a multidecade decline, which began moderating in the 1990s, and that annual reproductive rate and natural calf survival rates rose over time in a density‐dependent manner. However, selected models were equivocal regarding whether the natural juvenile survival rate was constant or decreasing over time. Depending on whether juvenile survival decreased after 1998, the population growth rate either increased during 1999–2015 or stabilized at a lesser level of decline than seen in the 1980s. The probability that the population was still declining in 2015 ranged from 45% to 87%.

Evaluation of a method using survey counts and tag data to estimate the number of Pacific walruses (Odobenus rosmarus divergens) using a coastal haulout in northwestern Alaska - Brian C. Battaile; Chadwick V. Jay; Mark S. Udevitz; Anthony S. Fischbach (Polar Biology, 2017)

Identifying a reliable blubber measurement site to assess body condition in a marine mammal with topographically variable blubber, the Pacific walrus - Shawn R. Noren; Mark S. Udevitz; Lisa Triggs; Jessa Paschke; Lisa Oland; Chadwick V. Jay (Marine Mammal Science, 2015)
Pacific walruses may be unable to meet caloric requirements in the changing Arctic ecosystem, which could affect body condition and have population‐level consequences. Body condition has historically been monitored by measuring blubber thickness over the xiphoid process (sternum). This may be an unreliable condition index because blubber at other sites along the body may be preferentially targeted to balance energetic demands. Animals in aquaria provided an opportunity for controlled study of how blubber topography is altered by caloric intake. Morphology, body mass, blubber thickness (21 sites), and caloric intake of five mature, nonpregnant, nonlactating female walruses were measured monthly (12 month minimum). Body condition (mass × standard length −1 ) was described by a model that included caloric intake and a seasonal effect, and scaled positively with estimates of total blubber mass. Blubber thicknesses (1.91–10.69 cm) varied topographically and were similar to values reported for free‐ranging female walruses. Body condition was most closely related to blubber thickness measured dorsomedially in the region of the anterior insertion of the pectoral flippers (shoulders); sternum blubber thickness was a relatively poor indicator of condition. This study demonstrates the importance of validating condition metrics before using them to monitor free‐ranging populations.

Demography of the Pacific walrus ( Odobenus rosmarus divergens ): 1974–2006 - Rebecca L. Taylor; Mark S. Udevitz (Marine Mammal Science, 2015)
Global climate change may fundamentally alter population dynamics of many species for which baseline population parameter estimates are imprecise or lacking. Historically, the Pacific walrus is thought to have been limited by harvest, but it may become limited by global warming‐induced reductions in sea ice. Loss of sea ice, on which walruses rest between foraging bouts, may reduce access to food, thus lowering vital rates. Rigorous walrus survival rate estimates do not exist, and other population parameter estimates are out of date or have well‐documented bias and imprecision. To provide useful population parameter estimates we developed a Bayesian, hidden process demographic model of walrus population dynamics from 1974 through 2006 that combined annual age‐specific harvest estimates with five population size estimates, six standing age structure estimates, and two reproductive rate estimates. Median density independent natural survival was high for juveniles (0.97) and adults (0.99), and annual density dependent vital rates rose from 0.06 to 0.11 for reproduction, 0.31 to 0.59 for survival of neonatal calves, and 0.39 to 0.85 for survival of older calves, concomitant with a population decline. This integrated population model provides a baseline for estimating changing population dynamics resulting from changing harvests or sea ice.

Potential population-level effects of increased haulout-related mortality of Pacific walrus calves - Mark S. Udevitz; Rebecca L. Taylor; Joel L. Garlich-Miller; Lori T. Quakenbush; Jonathan A. Snyder (Polar Biology, 2013)

Estimating survival rates with time series of standing age‐structure data - Mark S. Udevitz; Peter J. P. Gogan (Ecology, 2012)
It has long been recognized that age‐structure data contain useful information for assessing the status and dynamics of wildlife populations. For example, age‐specific survival rates can be estimated with just a single sample from the age distribution of a stable, stationary population. For a population that is not stable, age‐specific survival rates can be estimated using techniques such as inverse methods that combine time series of age‐structure data with other demographic data. However, estimation of survival rates using these methods typically requires numerical optimization, a relatively long time series of data, and smoothing or other constraints to provide useful estimates. We developed general models for possibly unstable populations that combine time series of age‐structure data with other demographic data to provide explicit maximum likelihood estimators of age‐specific survival rates with as few as two years of data. As an example, we applied these methods to estimate survival rates for female bison ( Bison bison ) in Yellowstone National Park, USA. This approach provides a simple tool for monitoring survival rates based on age‐structure data.

Results and evaluation of a survey to estimate Pacific walrus population size, 2006 1 - Suzann G. Speckman; Vladimir I. Chernook; Douglas M. Burn; Mark S. Udevitz; Anatoly A. Kochnev; Alexander Vasilev; Chadwick V. Jay; Alexander Lisovsky; Anthony S. Fischbach; R. Bradley Benter (Marine Mammal Science, 2011)
In spring 2006, we conducted a collaborative U.S.–Russia survey to estimate abundance of the Pacific walrus ( Odobenus rosmarus divergens ). The Bering Sea was partitioned into survey blocks, and a systematic random sample of transects within a subset of the blocks was surveyed with airborne thermal scanners using standard strip‐transect methodology. Counts of walruses in photographed groups were used to model the relation between thermal signatures and the number of walruses in groups, which was used to estimate the number of walruses in groups that were detected by the scanner but not photographed. We also modeled the probability of thermally detecting various‐sized walrus groups to estimate the number of walruses in groups undetected by the scanner. We used data from radio‐tagged walruses to adjust on‐ice estimates to account for walruses in the water during the survey. The estimated area of available habitat averaged 668,000 km 2 and the area of surveyed blocks was 318,204 km 2 . The number of Pacific walruses within the surveyed area was estimated at 129,000 with 95% confidence limits of 55,000–507,000 individuals. Poor weather conditions precluded surveying in other areas; therefore, this value represents the number of Pacific walruses within about half of potential walrus habitat.

Estimation of walrus populations on sea ice with infrared imagery and aerial photography - Mark S. Udevitz; Douglas M. Burn; Marc A. Webber (Marine Mammal Science, 2008)
Population sizes of ice‐associated pinnipeds have often been estimated with visual or photographic aerial surveys, but these methods require relatively slow speeds and low altitudes, limiting the area they can cover. Recent developments in infrared imagery and its integration with digital photography could allow substantially larger areas to be surveyed and more accurate enumeration of individuals, thereby solving major problems with previous survey methods. We conducted a trial survey in April 2003 to estimate the number of Pacific walruses ( Odobenus rosmarus divergens ) hauled out on sea ice around St. Lawrence Island, Alaska. The survey used high altitude infrared imagery to detect groups of walruses on strip transects. Low altitude digital photography was used to determine the number of walruses in a sample of detected groups and calibrate the infrared imagery for estimating the total number of walruses. We propose a survey design incorporating this approach with satellite radio telemetry to estimate the proportion of the population in the water and additional low‐level flights to estimate the proportion of the hauled‐out population in groups too small to be detected in the infrared imagery. We believe that this approach offers the potential for obtaining reliable population estimates for walruses and other ice‐associated pinnipeds.

COMPARISON OF METHODS USED TO ESTIMATE NUMBERS OF WALRUSES ON SEA ICE - Mark S. Udevitz; James R. Gilbert; Gennadii A. Fedoseev (Marine Mammal Science, 2001)
A bstract The US and former USSR conducted joint surveys of Pacific walruses on sea ice and at land haul‐outs in 1975, 1980, 1985, and 1990. One of the difficulties in interpreting results of these surveys has been that, except for the 1990 survey, the Americans and Soviets used different methods for estimating population size from their respective portions of the sea ice data. We used data exchanged between Sovier and American scientists to compare and evaluate the two estimation procedures and to derive a set of alternative estimates from the 1975, 1980, and 1985 surveys based on a single consistent procedure. Estimation method had only a small effect on total population estimates because most walruses were found at land haul‐outs. However, the Sovievr method is subject to bias that depends on the distribution of the population on the sea ice and this has important implications for interpreting the ice portions of previously reported surveys for walruses and other pinniped species. We recommend that the American method be used in future surveys. Future research on survey methods for walruses should focus on other potential sources of bias and variation.